KOREOGRAFI TARI SUFI KOMUNITAS DZIKIR ZHAUWIYAH KECAMATAN KARTOSURO KABUPATEN SUKOHARJO - Safran Rusmalla; Setya Widyawati (Greget, 2019)
This research is a discussion on Sufi dance on Dzikir Zhauwiyah community. The problem in this study is the form of presentation, function and existence of Sufi dance. To discuss the issue using Sumandyo Hadi’s thoughts on dance elements consisting of elements combined into one, the staple elements of dance consist of 1) motion dance, explaining the motion used for example dance traditions or Kerakyatan, modern or creations, 2) floor patterns/Dance room, 3) dance music, 4) dance titles, 5) dance themes, 6) dancers (number and sex), 7) makeup costumes. To discuss about the function of Sufi dance using the thought of S. D Humardani which mentions that the dance function consists of primary and secondary functions. The results showed that Sufi dance choreography has meaning about the particles in the universe rotating around the sun in a direction to the left. Sufi Dance has a primary function namely as an aesthetic expression while its secondary function is as a means of ritual, meditation, therapy and media dhikr and da’wah function of the function shows that Sufi dance has a existence in the wider community. Keywords: dance, Sufi, Dzikir Zhauwiyah community.